Peran Pengurus Pondok Pesantren Dalam Pembinaan Karakter Kedisiplinan Santri di Pondok Thoriqul Huda Ponorogo - Ningsih, Ruddat Ilaina Surya; Sunarto; Utami, Prihma Sinta (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
This study aims to: 1) find out the role of boarding school administrators in fostering the character of students in the disciplines of Pondok Thoriqul Huda Ponorogo; 2) Knowing the forms of character building for students in the disciplines of Pondok Thoriqul Huda Ponorogo. This research is qualitative. The primary data source is the head of the boarding school and the board of management of the Thoriqul Huda boarding school. Data collection techniques in this study were observation, interviews, and documentation. The data analysis technique is data reduction, data presentation, and data conclusion. The results of this study can be seen that 1) the role of the board administrators in fostering the disciplinary character of students, namely: a) awakening students to perform congregational prayers at asr and dawn; b) guiding the students in carrying out activities in the Islamic Boarding School; c) discipline the students in the departure of the judiciary; d) impose sanctions on students who violate the rules of the order of the cottage; e) motivating students to study harder in Islamic boarding schools, while the role played by board administrators is active. Furthermore, the results of the second research) form the formation of students’ disciplinary character through a participatory approach, the form of guidance is divided into two, namely: a) socialization of the rules of the boarding school when students register at the cottage witnessed by parents; b) routine or programmed socialization once a month precisely on the fourth week or called yaumul reckoning for the students.